(untitled) (Tạp chí Y học Cộng đồng, 2026)
The psychological crisis of Generation Z has become an increasingly critical issue amidst a modern workplace undergoing profound technological, social, and cultural transformations. Today’s youth face not only professional demands but also the impacts of social media, comparison culture, success pressure, and an always-online environment. This review aims to synthesize and analyze research regarding psychological crises in Gen Z within the modern workforce, evaluating factors that exacerbate stress, anxiety, and occupational burnout. Adopting a Narrative Review methodology, literature was sourced from PubMed, Google Scholar, and ScienceDirect (2015–2025) using keywords related to Gen Z, mental health, social media, burnout, and future anxiety. Synthesized findings indicate that several determinants contribute to Gen Z’s psychological crises, including occupational burnout, social media comparison, future anxiety, the quarter-life crisis, hustle culture, and constant digital connectivity. These factors intensify emotional exhaustion, anxiety, diminished self-worth, and psychological distress. In conclusion, the psychological crisis of Generation Z is not merely an individual issue but a reflection of shifts in modern society and digitized environments. Supporting youth mental health requires a multidimensional approach to foster healthier workplace and societal frameworks.